Green fluorescent protein as a screenable marker to increase the efficiency of generating transgenic woody fruit plants - Ghorbel, R.; Juárez, José; Navarro, Luis; Pena, Leandro (2017)
The green fluorescent protein (GFP) from Aequorea victoria has been introduced into three different citrus genotypes [Citrus aurantium L., C. aurantifolia (Christm.) Swing. and C. sinensis L. Osbeck x Poncirus trifoliata (L.) Raf.] which are considered recalcitrant to transformation, mainly due to low transformation frequencies and to the regeneration of escape shoots at high frequencies from the Agrobacterium-inoculated explants. High-level GFP expression was detected in transgenic cells, tissues and plants. Using GFP as a vital marker has allowed us to localize the sites of transgene expression in specific cells, always occurring in callus tissue formed from the cambium of the cut ends of explants. Whereas green fluorescent shoots regenerated in all cases from this callus, most escapes regenerated directly from explants with almost no callus formation. Thus, development of callus from cambium is a prerequisite for citrus transformation. Furthermore, in vivo monitoring of GFP expression permitted a rapid and easy discrimination of transgenic and escape shoots. The selection of transgenic shoots could be easily favored by eliminating the escapes and/or by performing shoot-tip grafting of the transgenic buds soon after their origin. GFP-expressing shoots have also been observed in citrus explants cocultivated with Agrobacterium but cultured in a medium without the selective agent kanamycin. This opens the possibility to rescue the transgenic sectors and to regenerate transgenic plants without using selectable marker genes conferring antibiotic or herbicide resistance, which is currently a topic of much discussion for the commercialization of transgenic plants.